OsMYB7 determines leaf angle at the late developmental stage of lamina joints in rice - Kim, Suk-Hwan; Yoon, Jungwon; Kim, Hanna; Lee, Sang-Ji; Kim, Taehoon; Kang, Kiyoon; Paek, Nam-Chon (Frontiers in Plant Science, 2023)
Leaf angle shapes plant architecture, allowing for optimal light interception to maximize photosynthesis and yield, and therefore is a crucial agronomic trait. Here, we show that the rice (Oryza sativa L.) R2R3-type MYB transcription factor OsMYB7 determines leaf angle in a developmental stage-specific manner. OsMYB7-overexpressing lines produced wide-angled leaves and osmyb7 knockout mutants exhibited erect leaves. This phenotype was restricted to the lamina joints at the late developmental stage. In agreement with these observations, OsMYB7 was preferentially expressed in the lamina joints of post-mature leaves. Since OsMYB7 homologs are transcriptional repressors of lignin biosynthesis, we examined whether OsMYB7 might inhibit thickening of secondary cell walls. Although OsMYB7 repressed lignin biosynthesis, it enhanced thickening of sclerenchyma cell walls by elevating cellulose contents at the lamina joints. Furthermore, we found that OsMYB7 affects endogenous auxin levels in lamina joints, and the adaxial cells of lamina joints in OsMYB7-overexpressing lines and osmyb7 knockout mutants exhibited enhanced and reduced elongation, respectively, compared to the wild type. These results suggest that OsMYB7 promotes leaf inclination partially through decreasing free auxin levels and promoting cell elongation at the adaxial side of lamina joints.